Cationic peptidopolysaccharides synthesized by 'click' chemistry with enhanced broad-spectrum antimicrobial activities. Issue 25 (17th May 2017) - Su, Yajuan; Tian, Liang; Yu, Meng; Gao, Qiang; Wang, Dehui; Xi, Yuewei; Yang, Peng; Lei, Bo; Ma, Peter X.; Li, Peng
Abstract : A series of broad-spectrum antimicrobial cationic peptidopolysaccharides have been synthesized using a facile thiol–ene 'click' chemistry. Abstract : The emergence and spread of multidrug-resistant (MDR) bacteria is a serious clinical problem, and a challenge for the medical research community. There is an urgent need to explore novel effective antimicrobial molecules. Here, we report on a series of cationic peptidopolysaccharides that have a bacterial peptidoglycan-mimetic structure and have been synthesized using a facile thiol–ene 'click' chemistry to graft antimicrobial peptides, ε-poly-l -lysine (EPL), onto a polysaccharide (chitosan, CS) backbone. These CS- g -EPL copolymers demonstrated enhanced, selective, broad-spectrum antibacterial and antifungal activities towards Gram-negative bacteria ( Escherichia coli and Pseudomonas aeruginosa ), Gram-positive bacteria ( Enterococcus faecalis and methicillin-resistant Staphylococcus aureus (MRSA)), and fungi ( Candida albicans and Fusarium solani ). Mechanistic studies proved that the CS- g -EPL likely disrupts the anionic microbial membrane leading to cell death, and is less likely to disrupt the mammalian cell membrane. In addition, CSL - g -EPL50% exhibits good in vitro biocompatibility with mammalian cells, and very little evidence of in vivo toxicity. Most importantly, CS- g -EPL demonstrated a strong antimicrobial efficacy with a log reduction of 4.66 in a rat MRSA infection model. These excellent biological properties present a promising prospect for CS- g -EPL in biomedical applications.